What drives Tadawul All Stock Index of the Saudi Stock Market - Arabi, Khalafalla Ahmed Mohamed (Archives of Business Research, 2018)
This paper aims to detect factors, which drive Tadawul All Stock Index (TASI) of the Saudi Stock Market during the period August 2005 May 2017. The application of Autoregressive Distributed Lag model (ARDL) and Bounds test revealed that there is no long-run relationship exist if consumer price index, interest rate, oil prices, general price level (P) and government expenditure are included in the model. While price-earnings ratio, nominal effective exchange rate (NEER), money supply (M3), and long term credit (L) relate significantly to TASI in both the short-run and long-run with an error correction term -0.22 i.e. disequilibrium takes four and half month to correct. Half of explanatory variables are fixed namely NEER, and L, while PE and M3 are dynamic. The GARCH model presented that news plays significant role in the volatility of stock market returns. Smaller GARCH term than ARCH indicates that a shock will take short time to die out.